Outcome following cosmetic rostral nasal reconstruction after planectomy in 26 dogs. Issue 1 (9th November 2018) - Dickerson, Vanna M.; Grimes, Janet A.; Vetter, Catherine A.; Colopy, Sara A.; Duval, Julie M.; Northrup, Nicole C.; Schmiedt, Chad W.
Abstract: Objective: To report the outcome and owner satisfaction after planectomy for nasal planum neoplasia with cosmetic reconstruction with bilateral labial mucocutaneous rotation flaps in dogs. Study design: Multi‐institutional, retrospective case series. Animals: Twenty‐six client‐owned dogs. Methods: Medical records were searched for dogs that had undergone the procedure. Signalment, diagnosis, surgery, complications, requirement for revision surgery, recurrence, and survival information were recorded. Owners were contacted by telephone about their dog's quality of life after the procedure and their satisfaction with their dog's outcome. Results: Twenty‐five dogs underwent radical planectomy, and 1 dog underwent resection of the nasal planum. Twenty‐four dogs had a diagnosis of squamous cell carcinoma, 1 had a diagnosis of atypical adenocarcinoma, and 1 had a diagnosis of a mast cell tumor. Complications occurred in 19 (73%) dogs, with 9 dogs requiring revision surgery; 1 dog not surviving to discharge. Median survival time was 1542 days (range, 3‐2010). Recurrence of the primary tumor was suspected in 2 (7.7%) dogs, both with narrow or incomplete excision. Among 11 owners interviewed, 10 were satisfied with their dog's appearance, and 8 reported they would consent to the procedure again. Conclusion: Dehiscence was common after this procedure, but local tumor control and survival times were excellent. Owner satisfaction was high, although preoperative client education is vital. Clinical significance: This technique should be considered as a viable option for dogs with nasal planum neoplasia given the high rate of recurrence with less aggressive treatment. Complications common following surgery, but do not persist long term and survival times were excellent.